2006
DOI: 10.21273/jashs.131.3.393
|View full text |Cite
|
Sign up to set email alerts
|

An Extended Linkage Map for Watermelon Based on SRAP, AFLP, SSR, ISSR, and RAPD Markers

Abstract: Seventy-one amplified fragment length polymorphism (AFLP), 93 sequence related amplified polymorphism (SRAP), and 14 simple sequence repeat (SSR) markers were used to extend an initial genetic linkage map for watermelon [Citrullus lanatus (Thunb.) Matsum. & Nakai]. The initial map was based on 151 randomly amplified polymorphic DNA (RAPD) and 30 and inter-simple sequence repeat (ISSR) markers. A testcross population previously used for mapping of RAPD and ISSR markers was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 37 publications
0
61
1
Order By: Relevance
“…Thirty-eight of the ESTs containing SSR motifs were used for primer pair design and developing EST-SSR markers for watermelon (Levi et al 2009). Here, these EST-PCR and EST-SSR primers developed for watermelon were used to amplify genomic DNA of several cucurbit species including Citrullus spp., Cucumis spp., Cucurbita spp., L. siceraria, B. hispida, and P. fistulosus PIs (Table 1), as shown in a procedure used for testing EST-PCR and EST-SSR primers in watermelon (Levi et al 2006a(Levi et al , 2009. The annealing temperature for each PCR experiment ranged from 52 to 59°C, based on the T m for each primer-pair (Levi et al 2009).…”
Section: Est Marker Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-eight of the ESTs containing SSR motifs were used for primer pair design and developing EST-SSR markers for watermelon (Levi et al 2009). Here, these EST-PCR and EST-SSR primers developed for watermelon were used to amplify genomic DNA of several cucurbit species including Citrullus spp., Cucumis spp., Cucurbita spp., L. siceraria, B. hispida, and P. fistulosus PIs (Table 1), as shown in a procedure used for testing EST-PCR and EST-SSR primers in watermelon (Levi et al 2006a(Levi et al , 2009. The annealing temperature for each PCR experiment ranged from 52 to 59°C, based on the T m for each primer-pair (Levi et al 2009).…”
Section: Est Marker Analysismentioning
confidence: 99%
“…The DNA markers were produced using EST-PCR and EST-SSR primers derived from watermelon sequences (Levi et al 2009) and SRAP primer pairs (Li and Quiros 2001) developed for watermelon (Levi et al 2006a(Levi et al , 2009). The EST-PCR, EST-SSR, and SRAP markers should represent gene sequence analogous across species.…”
Section: Introductionmentioning
confidence: 99%
“…The three maps were used to construct a consensus map containing 388 SNP markers. SSR, amplified fragment length polymorphism (AFLP) and single nucleotide polymorphism (SNP) markers were used as the main markers to construct the linkage maps in watermelon according to previous studies (Zhang et al 2004;Levi et al 2006). However, only a few studies have reported using CAPS markers as the main markers to construct the linkage map and detect QTLs in watermelon.…”
Section: Introductionmentioning
confidence: 99%
“…For example, of 1,309 RAPD markers, only 75 were polymorphic (5.9%) between two watermelon breeding lines (Harris et al 2008). Other marker systems such as AFLP (Che et al 2003;Levi et al 2004), SRAP (Levi et al 2006;Zhang et al 2008), EST-PCR (Levi et al 2009) and HFO-TAG produced slightly higher polymorphism among watermelon cultivars than the RAPD markers, but all in general were not breeder friendly. Results from these genetic assays were hardly comparable due to lack of a common core set of reference genotypes and the use of different marker systems.…”
Section: Introductionmentioning
confidence: 99%
“…In watermelon, SSRs have recently been used for germplasm characterization (Jarret et al 1997;Guerra-Sanz 2002;Mujaju et al 2010), evaluation of genetic diversity (Padmavathi et al 2010), germplasm management (Zhang et al 2010), cultivar identification (Levi et al 2009), and genetic mapping (Levi et al 2006). For cultivar identification, evaluation of genetic diversity or whole genome genetic mapping studies, full coverage of representative SSRs is needed.…”
Section: Introductionmentioning
confidence: 99%